Moyamoya Disease Explored Through RNF213 : Genetics, Molecular Pathology, and Clinical Sciences - Koizumi, Akio; Nagata, Kazuhiro; Houkin, Kiyohiro; Tominaga, Teiji; Miyamoto, Susumu; Kure, Shigeo; Tournier-Lasserve, Elizabeth (Springer Singapore : Imprint: Springer, 2017)
This book presents the latest findings on biological, epidemiological, and clinical investigations of RNF213, which is thought to be involved in many biological processes and plays a key role in cerebro- and cardiovascular disease . By discussing the epidemiology and genetic epidemiology of the disease with a particular focus on the molecular function of RNF213, research using animal models, diagnosis, therapy and clinical management around the world, this work makes a valuable contribution to the study of the disease. Moyamoya Disease Explored Through RNF213 is an indispensable resource for both beginning and experienced researchers, pediatricians, neurologists, and neurosurgeons who are seeking comprehensive information on adult and childhood stroke.
Keywords: Medicine.; Public health.; Neurology.; Neurosurgery.; elektronické knihy; electronic books